Drivers of Entrepreneurship and Post-Entry Performance : Microeconomic Evidence from Advanced and Developing Countries - Vivarelli, Marco (World Bank, Washington, DC, 2013)
The aim of this study is to provide a microeconomic investigation of the concept of entrepreneurship; in particular, it discusses the following issues: 1) the alternative ways of looking at entrepreneurship, distinguishing "creative destruction" from simple "turbulence"; 2) the different microeconomic determinants of new firm formation, distinguishing "progressive" from "regressive" drivers; 3) the relationship between ex-ante characteristics (of the founder) and post-entry performance (of the new firm); and 4) the possible scope for an economic policy aimed at maximizing the impact of entrepreneurship on economic growth. Where possible and appropriate, the paper devotes particular attention to the specific features characterizing entrepreneurship in developing countries.